Carved in stone [large type] - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Blackstone legacy, 2021)
"Kellerman now lives a quiet life as a botanist at an idyllic New York college. She largely ignores her status as heiress to the infamous Blackstone dynasty and hopes to keep her family's heartbreak and scandal behind her. Patrick O'Neill survived a hardscrabble youth to become a lawyer for the downtrodden Irish immigrants in his community. He's proud of his work, even though he struggles to afford his ramshackle law office. All that changes when he accepts a case that is sure to emphasize the Blackstones' legacy of greed and corruption by resurrecting a thirty-year-old mystery. Little does Patrick suspect that the Blackstones will launch their most sympathetic family member to derail him. Gwen is tasked with getting Patrick to drop the case, but the old mystery takes a shocking twist neither of them saw coming. Now, as they navigate a burgeoning attraction and growing danger, Patrick and Gwen will be forced to decide if the risk to the life they've always held dear is worth the reward." --